“Doing the unexpected” – Study of Citizenship Behaviour of Police Personnel in India. - Arfath Hossain Amin, Bipul Prasad Kar; Dipanjana Sil, Sudipta Majumdar; Amar Kumar Mishra (Journal of Informatics Education and Research, 2025)
The pandemic COVID has engulfed the entire world in general and India in particular for the last year. Almost the entire country is under lockdown now and then forcing the people to stay inside their home for the safety of self and others. There is one section, though, which is braving against all odds not only to ensure a law-and-order situation but also educate and persuade the mass. This has necessitated the police personnel to go an extra mile reflecting a sense of responsibility towards citizens, colleagues, organizations, and nation and discharge their duties performing activities beyond the formal job descriptions, formal reward system, or direct and explicit recognition. In the present study, the researchers have explored the antecedents and empirically investigated the nature, extent, and mechanism of the impact of these variables that lead to the police personnel displaying the organizational citizenship behavior at this unprecedented juncture of time in India.